The influence of Behavior, Attitude, and Entrepreneurial education on Entrepreneurial Interest among Students in West Jakarta - Rodhiah Rodhiah; Nur Hidayah (Sultan Publisher, 2024)
Interest in entrepreneurship is an individual choice due to their courage to take risks in building, developing, and facing challenges in business. This research examines the influence of behaviour, attitudes, and entrepreneurship education on entrepreneurial interest among students. Related to several previous studies, various internal and external factors that influence an individual's entrepreneurial intention have been identified. Internal factors may include an individual's attitudes and behaviours, while external factors encompass the entrepreneurial education that a person receives. The respondents in this study are fifth-semester students in West Jakarta, specifically from the Faculty of Economics and Business. The sampling technique is purposive sampling. The data collection used is a survey accompanied by an open-ended questionnaire as the instrument. The distribution of the questionnaire can be conducted both online and offline—with a quantitative descriptive analysis technique using regression analysis and Partial Least Square (PLS) program analysis version 3.00. The results indicate that behavioural control has a negative and insignificant effect on entrepreneurial interest. Attitude has a positive but not significant influence on interest in entrepreneurship. Entrepreneurship education has a positive and significant impact on entrepreneurial interest among students.